French as a foreign language learners’ metacognitive strategy: A comparative study between Indonesia, Thailand, and Vietnam - Pranowo, Dwiyanto Djoko; Tobing, Roswita Lumban; Herman, Herman; Van, Cong Tran (Indonesian Journal of Applied Linguistics, 2024)
Metacognition is central to language learning because it encompasses the processes that govern the efficient use of learning strategies. It is especially important as a way to address language learners’ issues of limited repertoire of strategies and their application. While much research on language learning strategies  have been related to the learning of English, this study observes the increasingly appealing French as an additional language hence French as a Foreign Language (FFL) is gaining importance. This research was carried out by examining some similarities and differences in models of learning strategies of FLE students in three ASEAN countries.  The present study aims to investigate into FFL learners’ metacognitive strategies which contribute to the development of learners’ autonomy, despite the different contexts of study in Indonesia, Thailand and Vietnam. This study is descriptive qualitative research involving 56 students from three universities in Bangkok (Thailand), Hanoi (Vietnam) and Yogyakarta (Indonesia) as an ad-hoc sample to study their French Language Education (FLE) learning strategies. Using a Metacognitive Strategy Questionnaire (MSQ), this study result in a few insights of FFL learning process. The participants showed a consistent metacognitive strategy in terms of planning, monitoring and evaluating. Even though they are located in different countries, these strategies are proved to contribute to their autonomy as an FFL learner with different specificities.